1979
DOI: 10.1177/154079697900400107
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Competency Indicators of Teachers of the Severely Handicapped

Abstract: This article describes a research effort designed to identify indicators of competencies of teachers of the severely handicapped. Two indicators of competency (amount of instruction time, percentage of curriculum materials task analyzed) were identified as contributing to 78% of the variance for all variables. A training model was described for teaching these competencies to teachers, and subsequent student performance data were reported which demonstrate that the students of teachers trained under this model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Special educators have advocated summer, or extended-year programs for students with severe handicaps, to reduce or eliminate the problem of summer forgetting. Fredericks et al (1978) found a positive relationship between amount of instructional time and achievement gains for students with severe handicaps. In a review of the literature on the efficacy of extended-year programs, Magliocca and Barker ( 1981) reported that the literature is replete with reports of summer programming for handicapped children, almost all indicating significant growth in one or another of the skill areas for different categories of handicapped conditions.…”
Section: Forgetting and Recoupmentmentioning
confidence: 85%
“…Special educators have advocated summer, or extended-year programs for students with severe handicaps, to reduce or eliminate the problem of summer forgetting. Fredericks et al (1978) found a positive relationship between amount of instructional time and achievement gains for students with severe handicaps. In a review of the literature on the efficacy of extended-year programs, Magliocca and Barker ( 1981) reported that the literature is replete with reports of summer programming for handicapped children, almost all indicating significant growth in one or another of the skill areas for different categories of handicapped conditions.…”
Section: Forgetting and Recoupmentmentioning
confidence: 85%
“…Fredericks et al (1979) found gains by severely handicapped students were related to percentage of task analyses conducted and the amount of time spent teaching. Koegel et al (1977) found the ability to use appropriate behavior management techniques was important and, more specifically, Katz et al (1977) reported the importance of teachers using successive approximation techniques.…”
Section: The Competenciesmentioning
confidence: 90%
“…Nearly all of the statements were made in reference to teachers of the &dquo;severely and profoundly&dquo; handicapped. Exceptions were writings that referred to the &dquo;severely handicapped&dquo;(Brown et al, 1979;Fredericks, Anderson, & Baldwin, 1979; Johnson, Flanagan, Burge, Kauffman-Debriere, & Spellman, 1980; …”
mentioning
confidence: 97%
“…Similar classroom instructional variables influence the acquisition of preacademic, language, motor, and self-help skills of severely handicapped children (Fredericks et al, 1979;Fredericks et al, 1982). Assuming that a similar relationship exists between instructional variables and acquisition of social skills-an unproven but testable hypothesis in itself-an implication drawn from academic instructional research is that teachers should schedule a substantial period of time for social skills instruction, plan specific activities (with measurable objectives), and provide a large number of opportunities for children to engage in social responses (or initiations).…”
Section: Scheduling Social Skills Instructionmentioning
confidence: 97%